2019
DOI: 10.1111/petr.13326
|View full text |Cite
|
Sign up to set email alerts
|

Single kidney transplantation from donors with acute kidney injury: A single‐center experience

Abstract: Introduction Despite a severe shortage of organ supply, patients are reluctant to accept organs from deceased donors with AKI, let alone from pediatric AKI donors. Methods We assessed 70 patients who received kidneys from donors with AKI (10 with pediatric and 60 with adult donors) and 176 contemporaneous patients who received kidneys from non‐AKI donors (41 with pediatric and 135 with adult donors) between March 2012 and February 2017 for retrospectively evaluating the clinical outcomes. Results AKI was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
10
2
Order By: Relevance
“…Prior research on the utilization of pediatric deceased donors with AKI was limited. Jiang et al [25] found that transplants procured from pediatric AKI donors have a comparable renal function and an excellent patient and graft survival rate, but they found a similar incidence of DGF, which is different from our study. In contrast, our study consists with another study includes very small (≤15 kg) pediatric donors with AKI and found that AKI can impact early post-transplant kidney graft function (e.g., the rate of DGF), but it did not increase the risk of early graft loss or decreased renal function in the long term [18] .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Prior research on the utilization of pediatric deceased donors with AKI was limited. Jiang et al [25] found that transplants procured from pediatric AKI donors have a comparable renal function and an excellent patient and graft survival rate, but they found a similar incidence of DGF, which is different from our study. In contrast, our study consists with another study includes very small (≤15 kg) pediatric donors with AKI and found that AKI can impact early post-transplant kidney graft function (e.g., the rate of DGF), but it did not increase the risk of early graft loss or decreased renal function in the long term [18] .…”
Section: Discussioncontrasting
confidence: 99%
“…The presence of AKI in organ donors appears to impact the willingness to accept and transplant donor kidneys in China [25] . The incidence rate of AKI ranges from 25% to 52% within pediatric intensive care units [26,27] , and to augment the donor pool with systematic analysis of kidney transplants from pediatric donors with AKI, we found that although the incidence of DGF was higher in recipients of allografts with AKI, deceased donor AKI status itself did not affect death-censored graft and recipient survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A particular problem may be posed by donors with AKI. Despite a high incidence of DGF, graft survival may be obtained, although with inferior outcomes to those observed with standard donors [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In the cases of successful kidney transplant from donors with AKI, it is possible that pretransplant, AKI was functional, being caused by the systemic and renal vasoconstriction related to the sympathetic overactivity and medications used to sustain circulation.…”
Section: Risk Factors For Dgfmentioning
confidence: 99%
“…The presence of AKI in organ donors appears to impact the willingness to accept and transplant donor kidneys in China [ 25 ]. The incidence rate of AKI ranges from 25 to 52% within pediatric intensive care units [ 26 , 27 ], and to augment the donor pool with systematic analysis of kidney transplants from pediatric donors with AKI, we found that although the incidence of DGF was higher in recipients of allografts with AKI, deceased donor AKI status itself did not affect death-censored graft and recipient survival.…”
Section: Discussionmentioning
confidence: 99%